Labor of persons sentenced to imprisonment: justification and theoretical issues - Abdizhami, A.Zh. (Bulletin of the Karaganda University “Law Series”, 2021)
Issues related to serving a sentence in the form of imprisonment require constant scientific and theoretical research. This is due to the fact that the punishment in the form of imprisonment is established as a type of punishment by the laws of many countries of the world. There is experience in attracting persons convicted in the execution of this punishment to work. In this regard, the question of whether the work of convicts is a right or an obligation is the source of many studies. The author of the article also tried to find an answer to this question, considering the problem based on the importance of highlighting the main signs of convict labor. With the help of these signs, we get the opportunity to bring the work of convicts as close as possible to the work of citizens at liberty. At the same time, professions that are mastered during the execution of sentences in institutions should be not only socially useful, but also useful after the expiration of the sentence. Historical comparability methods have been applied in order to study the effectiveness of the modernizationof the penitentiary system in the country in the direction of bringing the institutions of the penitentiary system closer to the requirements of the lowest international standards for the detention of convicts as ways of alienating the labor of convicts from such categories as torture, exploitation, slave labor. Concurrently, the work of the administration of the institution to activate the work of production and economic enterprises should be a guarantee of maximum convergence of the labor of convicted persons with the labor of freed persons. In conclusion, the work of convicts is considered as an imperative norm of criminal executive law, and the work carried out within the framework of a public–private partnership allows to analyze it as the right of convicts to the freedom to choose the type of work.